Kościół w Polsce represjonowany przez władze komunistyczne w latach 1944-1989 - Dębiński, Józef (Archiwa, Biblioteki i Muzea Kościelne, 2012)
After the Second World War, Poland underwent the process of Sovietisation. The entire activity of the new authority was confined to the collectivization of agriculture and the fight with the Church. It is true that in the years 1944-1947 the authorities adopted a relatively liberal policy towards the Church, which did not exclude, however, repression against clandestine activities of the clergy, and even assassinations. Soon, an open dispute arose between the authorities and the Episcopate, which was caused, among other things, by the cancellation of the concordat, the decree establishing the obligation of civil marriages and authorities’ interference in the church administration on the Recovered Territories (Western and Northern part of Poland). The communist authorities denounced the Catholic clergy for pathological hostility towards communism and post-war reality. Without good reason, they accused the Church of using the pulpit and confessional in this fight and supporting anti-communist underground. The period of severe repression against the Church lasted in the years 1948-1955 . It was the period of arrests, trials and bishops’ removal from their dioceses. To fight with the Church, the authorities created a separate Department IV in the Ministry of Home Affairs, whose structure survived until the fall of the Communism. The whole clergy was under control. Their activities were documented in the fi les of the operational records; from 1963 each clerical student joining the seminary had his fi le. The authorities also restricted the activities of the Catholic University of Lublin and created the Academy of Catholic Theology from the departments in Krakow and Warsaw. In addition, seminarists were obliged to do military service, the aim of which was to disorganize the teaching at the seminary. To settle the conflict in relations between the state and the Church, the Mixed Commission was established at the initiative of. Its purpose was to resolve conflict issues. In fact, despite the signed agreement, the communist authorities did not keep their commitments from the beginning. They started subversive activities in the Church, forming the movement of the “patriotic priests” attached to The Society of Fighters for Freedom and Democracy. They were given, among other things, the stolen property of the charitable church organization “Caritas”. Throughout the whole period of the Communism in Poland (1944-1989) the authorities used repression against 704 diocesan priests and 211 monks. Repressive measures of the Communists against the Church, which lasted from the end of the Second World War to 1989, are part of the martyrdom of the Catholic Church in the 20th century. In the following years only the methods and means changed in the fight with the Church, the essence remained always the same-to remove religion from public life.